A new experimental model for inducing interstitial cystitis by oxidative stress using intravesical instillation of a nitric oxide donor gel - Palma,Thais Figueiredo (2010)
ABSTRACT Objective: The aim of this study was to develop an experimental model of inducing interstitial cystitis through intravesical instillation of a polymeric solution containing the NO donor S-nitrousglutathione (GSNO) and to compare it to the experimental interstitial cystitis induced by vesical instillation of protamine and potassium chloride. Methods: A total of 40 female Wistar rats were used and divided into four groups: 1 – ten rats treated with saline solution + GSNO; 2 – ten rats treated with saline solution + polymeric solution (without GNSO); 3 – ten rats treated with protamine sulphate + KCl; 4 – ten rats treated with protamine sulphate + GSNO. The rats received one application (five animals in each group) or three applications (five animals in each group) of the corresponding substance through intravesical instillation, and after six days (five animals in each group) or nine days (five animals in each group) they were euthanized and their bladders were removed for macroscopic evaluation and histological study. Results: In the macroscopic evaluation edema and hyperemia of the mucosa were observed in 2 (22%) animals in Group 1, in no (0%) animal in Group 2, in 10 (100%) animals in Group 3, and in 5 (50%) animals in Group 4. In the protamine + KCl group and in saline + GSNO, similar effects were observed in the bladder wall. The animals in Group 2 (saline + polymeric solution) showed significantly less vascular congestion compared to the other groups after 9 days of the instillation (p = 0.0035). Significant fibrosis was observed in Groups 3 and 4, 6 days (p = 0.3781) and 9 days (p = 0.0459) after instillations, when compared to controls (Group 2). All groups presented neutrophilic infiltrate of variable intensity, 6 days after instillations (p = 0.7277). After 9 days, there was a regression of the infiltrate, with no evidence of accentuated neutrophilic reaction in all the groups (p = 0.2301). Conclusions: The inflammatory response to bladder instillation with an aqueous solution of S-nitrousglutathione was very similar to that induced by bladder instillation of protamine and KCl. Instillation of an aqueous solution of S-nitrousglutathione can be considered a new model for experimental induction of interstitial cystitis.